A prospective, real‐world, clinical pharmacokinetic study to inform lacosamide dosing in critically ill patients undergoing continuous venovenous haemofiltration (PADRE‐02). Issue 11 (5th May 2021) - Kalaria, Shamir N.; Armahizer, Michael; McCarthy, Paul; Badjatia, Neeraj; Gobburu, Jogarao V.; Gopalakrishnan, Mathangi
Abstract : Aims: Although the use of continuous renal replacement therapy (CRRT) has increased, limited dosing information exists on the effect of CRRT on antiepileptic drug pharmacokinetics. The objectives of this practice‐based study are to evaluate the pharmacokinetics of lacosamide and recommend individualized dosing recommendations in critically ill patients receiving continuous venovenous haemofiltration (CVVH). Methods: Seven patients receiving lacosamide and CVVH in a neurocritical care unit were enrolled. Pre‐filter, post‐filter and ultrafiltrate samples were obtained at baseline, right after the completion of the infusion, and up to six additional sampling time points post‐administration. Patient‐specific flow rates and clinical measures were also collected simultaneously at the time of sampling. Plasma concentrations were measured using a validated high‐performance liquid chromatography with ultraviolet radiation detection (HPLC‐UV) bioanalytical method. Non‐compartmental analysis was utilized to characterize the pharmacokinetics of lacosamide. Results: The observed mean sieving coefficient for lacosamide was 0.80 ± 0.10, suggesting high removal of lacosamide. Concentrations measured in six out of seven patients were observed to be outside the therapeutic range (5–12 mg/L). The estimated average volume of distribution was found to be similar to healthy patients (0.58 L/kg). The mean bias and precision of the estimated total clearance was −2.53% and 14.9%, respectively. Simulations of various doses suggest that effluent flow rate‐based dosing regimens could be used to individualize lacosamide therapeutics. Conclusions: CVVH clearance contributed a major fraction of the total lacosamide clearance in neurocritically ill patients. Given that drug clearance increases with higher effluent flow rates, lacosamide dosing regimens should be increased to match exposures observed in patients with normal renal function.